Molecular dynamics method for numerical study of thermal performance of hexacosane PCM in a Cu-nanochannel - Le, Quynh Hoang; Sajadi, S. Mohammad; Abdelmalek, Zahra; Karooby, Elaheh; Ghahderijani, Mehdi Jamali; Koochaki, Amin; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Due to the growth of energy consumption in world and limitation of fossil fuels, energy storage is of great importance. The n-Hexacosane (paraffin) is one of the most popular phase-change materials (PCMs) due to its high energy storage and low cost. Due to the number of carbon atoms, this structure reveals a wide phase transition temperature (Temp) range. In current research, thermal behavior (TB) of this PCM in a copper nanochannel investigated using molecular dynamics (MD) simulation. Also, initial Temp's effect on PCM's atomic behavior (AB) and TB investigated. Density (Dens), Temp, velocity (Vel) profiles, heat flux (HF), and thermal conductivity (TC) calculated to investigate studied structure's AB and TB. The obtained result reveals that TB of structure is improved by increasing initial Temp. Numerically, the Max-Vel and Temp from 0.0124 angstrom/ fs and 329.41 K to 0.0139 angstrom/fs and 364.29 K by increasing initial Temp from 300 to 350 K, and TC and HF increased from 0.254 W/mK and 387.325 W/m2 to 0.275 W/mK and 411.023 W/m2, respectively. This increase is due to the increase in interatomic collisions with increasing Temp. By increasing number and intensity of collisions, amount of structure's heat transferred (HT) also rises; hence, TB of atomic samples improves.
Keywords: Phase change materials; n-Hexacosane; Paraffin; Molecular dynamics simulation